Family Care Partners and Paid Caregivers: National Estimates of Role-Sharing in Home Care. - Fabius, Chanee D; Gallo, Joseph J; Burgdorf, JuliaG; Samus, Quincy M; Skehan, Maureen; Stockwell, Ian; Wolff, Jennifer L (Gerontologist, 2025)
Background and Objectives We describe "role-sharing" in home care, defined as family care partners and paid caregivers assisting with the same task(s). Research Design and Methods We studied 440 participants in the 2015 National Health and Aging Trends Study receiving paid help with self-care, mobility, or medical care. We describe patterns in receiving paid help only, help from care partners only, and role-sharing. We examine whether sole reliance on paid help or role-sharing differs by Medicaid-enrollment and dementia status. Results Half (52.9%) of care networks involved role-sharing. Care networks involving role-sharing more often occurred among older adults with dementia (48.7% vs 25.6%, p < .001) and less often for those who were Medicaid-enrolled (32.1% vs 49.4%, p < .01). Those living with dementia more often experienced role-sharing in eating (odds ratio [OR] 3.9 [95% confidence interval CI 1.20, 8.50]), bathing (OR 2.7, [95% CI 1.50, 4.96]), dressing (OR 2.1 [95% CI 1.14, 3.86]), toileting (OR 2.9 [95% CI 1.23, 6.74]), and indoor mobility (OR 2.8 [95% CI 1.42, 5.56]), and less often received help solely from paid helpers with medication administration (OR 0.24, [95% CI.12,.46]). Medicaid-enrollees more often received paid help only in dressing (OR 2.0 [95% CI 1.12, 3.74]), outdoor (OR 2.4 [95% CI 1.28, 4.36]), and indoor mobility (OR 4.3 [95% CI 2.41, 7.62]), and with doctor visits (OR 2.8 [95% CI 1.29, 5.94]). Discussion and Implications Role-sharing is common, especially among older adults living with dementia who are not Medicaid-enrolled. Strategies supporting information sharing and collaboration in home-based care merit investigation.